IMPLEMENTASI SISTEM INFORMASI PEMERINTAHAN DAERAH DALAM PENYUSUNAN ANGGARAN UNTUK MENINGKATKAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI KABUPATEN BOGOR PROVINSI JAWA BARAT - Asep Hendra; Rivaldi Pradana (Post Graduate School of Government Science, 2023)
Abstract The Indonesian government issued Regulation of the Minister of Home Affairs Number 70 of 2019 as an innovation made to facilitate regional financial management is the Regional Government Information System (SIPD). Following up on this regulation, the Regional Government Information System (SIPD) was started by the Regional Financial and Asset Management Agency (BPKAD) of Bogor Regency in preparing the budget. This study aims to measure the implementation of the local government information system (SIPD) in preparing the budget to improve the quality of local government financial reports in Bogor Regency, West Java Province. The research method used in this research is descriptive qualitative with an inductive approach. The data used in this study are primary data and secondary data. Data collection techniques used were interviews and documentation. The results of this study indicate that the implementation of local government information systems in preparing this budget has not gone well because there are still several obstacles and problems encountered that hinder the implementation process such as lack of socialization, limited knowledge, servers that are difficult to access. Keywords:, Budget Preparation, Implementation, Local Government Information System